2014
DOI: 10.1155/2014/959206
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Virulence Factors Genes inEscherichia coliIsolates from Women with Urinary Tract Infection in Mexico

Abstract: E coli isolates (108) from Mexican women, clinically diagnosed with urinary tract infection, were screened to identify virulence genes, phylogenetic groups, and antibiotic resistance. Isolates were identified by MicroScan4 system; additionally, the minimum inhibitory concentration (MIC) was assessed. The phylogenetic groups and 16 virulence genes encoding adhesins, toxins, siderophores, lipopolysaccharide (LPS), and invasins were identified by PCR. Phylogenetic groups distribution was as follows: B1 9.3%, A 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
43
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 43 publications
16
43
8
1
Order By: Relevance
“…Comparing across groups, the virulence genes were found in the strains of phylogenetic groups D and B1, and most frequently in group B2. Our results are confirmed in other studies [7,40].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Comparing across groups, the virulence genes were found in the strains of phylogenetic groups D and B1, and most frequently in group B2. Our results are confirmed in other studies [7,40].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 41.9% of the UPEC strains showed resistance to CIP. These results correspond to those of other studies conducted by López-Banda et al [7] and Giray et al [44], who reported 62.3% and 47% resistance in E. coli to CIP, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Treatment of UTIs generally includes β-lactam antibiotics, fluoroquinolones, nitrofurantoin or trimethoprim/sulfametoxazole (TMP/ SMX). Treatment varies according to patient age and gender, pathogen implicated, course of disease, and the anatomical area of the urinary tract involved [3,13]. While these drugs are successful in resolving some UTIs, resistance to commonly prescribed antimicrobial agents is a matter of increasing concern.…”
Section: Introductionmentioning
confidence: 99%